Encampments in Thunder Bay, Ontario: Characteristics, needs, and community-based approaches to reduce homelessness and encampments - Fu, Pengfei; Wilkinson, Ashley; Mago, Vijay; Krysowaty, Bonnie; Schiff, Rebecca (Canadian Planning and Policy / Aménagement et politique au Canada, 2026)
Governments and communities have long struggled to confront the persistent challenge of encampments, a direct outcome of homelessness. In recent years, North America and Europe have relied primarily on punitive laws and coercive practices, such as camp evictions involving police and bulldozers, to manage outdoor homelessness. These measures, however, disregard human rights, particularly those of Indigenous communities, and expose the tension between public order policies and basic survival needs. This study examines a period in January 2024, when Thunder Bay witnessed the voluntary and complete departure of individuals from encampments without coercion or forced removal. Unlike many cities that depend on punitive approaches, Thunder Bay succeeded through a collaborative, community-led strategy supported by temporary winter funding. Yet, when this funding ended in March 2024, encampments resurfaced, underscoring the necessity of sustained investment in non-coercive housing solutions. The case emphasizes the importance of long-term funding and supportive networks in addressing homelessness.